International Agricultural and Extension Education: Meeting the Unknown Challenges of Tomorrow - James R. Linder (Journal of International Agricultural and Extension Education, 2018)
The purpose of this paper is to provide philosophical observations and reflections over 25 years of the Journal of International Agricultural and Extension Education(JIAEE) as a reader, author, and editor. The paper provides a brief history of JIAEE including changes that occurred over the years. This paper honors those that contributed to JIAEE and stood as its caretakers over the past 25 years. This main body of the paper is divided into three sections: early years, middle years, and contemporary years. The paper exploresthe development and use of JIAEE keywords and provides visual depictions using wordclouds. The purpose of keywords is discussed and suggestions for future use are provided. Final recommendations and well wishes for the future are provided. Recommendations include: Considering the hiring of a permanent editor or publishing firm such as Taylor & Francis; creating a purposeful research agenda in conjunction with AIAEE; and redressing the developing and use of keywords
Keywords: Keywords; JIAEE; managing change; partnerships; & amp; historical